Tailoring the ligand shell for the control of cellular uptake and optical properties of nanocrystals - Ostermann, Johannes; Schmidtke, Christian; Wolter, Christopher; Merkl, Jan-Philip; Kloust, Hauke; Weller, Horst (Beilstein Journal of Nanotechnology, 2015)
In this short review, the main challenges in the use of hydrophobic nanoparticles in biomedical application are addressed. It is shown how to overcome the different issues by the use of a polymeric encapsulation system, based on an amphiphilic polyisoprene-block-poly(ethylene glycol) diblock copolymer. On the basis of this simple molecule, the development of a versatile and powerful phase transfer strategy is summarized, focusing on the main advantages like the adjustable size, the retained properties, the excellent shielding and the diverse functionalization properties of the encapsulated nanoparticles. Finally, the extraordinary properties of these encapsulated nanoparticles in terms of toxicity and specificity in a broad in vitro test is demonstrated.
Keywords: biolable; cellular uptake; fluorescence quenching; poylmeric micelles; quantum dots